Semiconducting polymer nanospherical nucleic acid probe for transcriptomic imaging of cancer chemo-immunotherapy - Xu, Cheng (2024)
Real-time in vivo imaging of RNA can enhance the understanding of physio-pathological processes. However, most nucleic acid-based sensors have poor resistance to nucleases and limited photophysical properties, making them suboptimal for this purpose. To address this, a semiconducting polymer nanospherical nucleic acid probe (SENSE) for transcriptomic imaging of cancer immunity in living mice is developed. SENSE comprises a semiconducting polymer (SP) backbone covalently linked with recognition DNA strands, which are complemented by dye-labeled signal DNA strands. Upon detection of targeted T lymphocyte transcript (Gzmb: granzyme B), the signal strands are released, leading to a fluorescence enhancement correlated to transcript levels with superb sensitivity. The always-on fluorescence of the SP core also serves as an internal reference for tracking SENSE uptake in tumors. Thus, SENSE has the dual-signal channel that enables ratiometric imaging of Gzmb transcripts in the tumor of living mice for evaluating chemo-immunotherapy; moreover, it has demonstrated sensitivity and specificity comparable to flow cytometry and quantitative polymerase chain reaction,  yet offering a faster and simpler means of T cell detection in resected tumors. Therefore, SENSE represents a promising tool for in vivo RNA imaging.